2005
DOI: 10.1177/0898010104272019
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Struggle

Abstract: Assessment of and assistance with managing spiritual struggle are necessary to promote QOL and life satisfaction among those facing difficult health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 43 publications
4
27
1
Order By: Relevance
“…Our finding of a higher likelihood of R/S struggle among those with 6 months or less since their diagnosis is consistent with some prior findings [23] but not all [18, 20, 37]. Further research is needed to clarify what factors impact the development and trajectory of R/S struggle.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding of a higher likelihood of R/S struggle among those with 6 months or less since their diagnosis is consistent with some prior findings [23] but not all [18, 20, 37]. Further research is needed to clarify what factors impact the development and trajectory of R/S struggle.…”
Section: Discussionsupporting
confidence: 91%
“…This acknowledged, current thought articulates three dimensions of R/S struggle or negative R/S coping: transpersonal (e.g., relationship with God), interpersonal (e.g., relationship with R/S community or leadership), and intrapersonal (e.g., meaning, doubt). The current standard for measuring R/S struggle is the negative religious coping subscale of the Brief RCOPE [17, 18, 20, 22, 23, 25]. Other measures of negative religious coping from the full RCOPE [33] have also been employed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the literature has shown inconsistent findings in the relationship between spiritual well-being and health outcomes, including psychological well-being outcomes [1014]. It is unclear whether spiritual well-being based coping may benefit or hinder cancer survivor’s psychological adjustment.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that spiritual well-being aids in the coping response by providing cancer patients with a framework to discover meaning and ascertain purpose in life despite occurrence of a potentially fatal disease [1113]. In contrast, other studies have reported that spiritual well-being may create distress in patients, possibly contributing to depression, if patients experience “spiritual conflict” where they question their beliefs and/or faith in God in the context of their disease [10,14]. …”
Section: Introductionmentioning
confidence: 99%